Fruit quality assessment based on mineral elements and juice properties in nine citrus cultivars - Jiao, Yiling; Zhang, Shuozhen; Jin, Haitao; Wang, Yuwen; Jia, Yamin; Zhang, Hua; Jiang, Yuying; Liao, Wenqiang; Chen, Li-Song; Guo, Jiuxin (Frontiers in Plant Science, 2023)
Introduction Citrus fruit is considered a superfood due to its multiple nutritional functions and health benefits. Quantitative analysis of the numerous quality characteristics of citrus fruit is required to promote its sustainable production and industrial utilization. However, little information is available on the comprehensive quality assessment of various fruit quality indicators in different citrus cultivars. Methods A total of nine different fresh citrus fruits containing seeds were collected as the experimental materials. The objectives of this study were: (i) to determine the morphological and juice properties of citrus fruits, (ii) to measure the mineral elements in the peel, pulp, and seeds, and (iii) to evaluate the fruit quality index (FQI) using the integrated quality index (IQI) and the Nemoro quality index (NQI) methods. Results There were significant differences in fruit quality characteristics, including morphological, mineral, and juice quality, among the investigated citrus cultivars. The proportion of pulp biomass was the highest, followed by that of peel and seeds. N and Cu had the highest and lowest concentrations, respectively, among the measured elements across all citrus fruits, and the amounts of N, P, Mg, Cu, and Zn in seeds, K and Al in pulp, and Ca, Fe, and Mn in peel were the highest, dramatically affecting the accumulation of minerals in the whole fruit and their distribution in various fruit parts. Additionally, Ningmeng fruits had the highest vitamin C and titratable acidity (TA) but the lowest total soluble solids (TSS) and total phenolic (TP) contents, resulting in the lowest TSS/TA and pH values. In contrast, Jinju fruits had the highest TSS and TP contents. Based on the mineral element and juice quality parameters, principal component analysis showed that the citrus fruits were well separated into four groups, and the dendrogram also showed four clusters with different distances. The FQI range based on the IQI method (FQIIQI) and NQI method (FQINQI) was 0.382-0.590 and 0.106-0.245, respectively, and a positive relationship between FQIIQI and FQINQI was observed. Conclusion Our results highlight the great differences in mineral and juice characteristics among fruit parts, which mediated fruit quality. The strategy of fruit quality assessment using the FQI can be expanded for targeted utilization in the citrus industry.